Motor Unit Force Potentiation and Calcium Handling Protein Concentration in Rat Fast Muscle After Resistance Training - Łochyński, Dawid; Kaczmarek, Dominik; Grześkowiak, Marcin; Majerczak, Joanna; Podgórski, Tomasz; Celichowski, Jan (Frontiers in Physiology, 2021)
Post-tetanic potentiation (PTP) of force depends on intramuscular Ca2+ levels and sensitivity, and may be affected by fatigue. The aim of this study was to determine the ability of isolated fast fatigue resistant (FR) and fast fatigable (FF) motor units (MUs) to potentiate force evoked with single and 40 Hz electrical stimulation after 5-week voluntary weight lifting training. Tetanic contractions evoked by gradually increasing (10-150 Hz) stimulation frequency served as conditioning stimulation. Additionally, the concentration of myosin light chain kinase and proteins engaged in calcium handling was measured in rat fast medial gastrocnemius muscle. After the training the potentiation of twitch force and peak rate of force development was increased in FF but not FR MUs. Force potentiation of 40 Hz tetanic contractions was increased in both fast MU types. After the training the twitch duration of FR MUs was decreased and FF MUs were less prone to high-frequency fatigue during conditioning stimulation. Muscle concentration of triadin was increased, whereas concentrations of ryanodine receptor 1, junctin, FKBP12, sarcoplasmic reticulum calcium ATPase 1, parvalbumin, myosin light chain kinase and actomyosin adenosine triphosphatase content were not modified. After short-term resistance training the twitch contraction time and twitch:tetanus force ratio of FR MUs are decreased and PTP ability is not changed. However, PTP capacity is increased in response to submaximal activation. In FF MUs increase in PTP ability coexists with lesser fatigability. Further work is required to find out if the increase in triadin concentration has any impact on the observed contractile response.